Depression, negative symptoms, social stagnation and social decline in the early course of schizophrenia - Häfner, Heinz; Löffler, Walter; Maurer, Kurt; Hambrecht, Martin; Heiden, Wolfram an der (Acta psychiatrica Scandinavica, 1999)
Häfner H, Löffler W, Maurer K, Hambrecht M, an der Heiden W. Depression, negative symptoms, social stagnation and social decline in the early course of schizophrenia. Acta Psychiatr Scand 1999: 100: 105-118. © Munksgaard 1999. Objective: The aim of this study was to investigate when social consequences in schizophrenia emerge, and what conditions give rise to the social disadvantage evident in people suffering from schizophrenia. Method: Early course in schizophrenia was studied in a population-based sample of 232 first illness-episode cases retrospectively from onset to first admission, and in a representative subsample of 115 patients prospec-tively at six cross-sections over a period of 5 years. Data on non-specific and negative symptomatology and social development was compared with data from an age- and sex-matched control group drawn from the normal population. Results: In total, 73% of the patients showed a prodromal phase of several years. First signs were depressive and negative symptoms. In 57% of cases social disability emerged 2 to 4 years before first admission. Social consequences depended on the level of social development at onset. An early onset involved social stagnation, and a late onset was associated with social decline. Men's poorer social outcome was determined by their lower level of social development at onset and socially adverse illness behaviour. The 5-year symptom-related course showed no gender difference. At 81′% the lifetime prevalence of depressive mood until first admission was several times higher in schizophrenics than in healthy controls. Early depression predicted a lower subsequent score for affective flattening. Suicide indicators were predicted by lack of self-confidence and feelings of guilt early in the illness. Conclusion: Taking into account a prodromal phase of several years on average before first hospital admission, early detection, case identification and intervention are urgently needed. The intervention must be targeted at syndromes such as early depression, negative symptoms and certain forms of cognitive and social impairment.
First published: 13 November 2007
Gesehen am 18.11.2020